Meningkatkan Kepuasan Pelanggan Melalui Peningkatan Mutu Dan Kualitas Produk Pada Kopi Konnichiwa Pamulang - Hananto, Djoko; Sulistiani, Dahlia Ayu; Syarifatunnisa, Mawaddah Azkiya; Fitrah, Vina Nur (EL-EMIR INSTITUTE, 2024)
This service was carried out at Konnichiwa Pamulang Coffee. The aim of this service is to increase customer satisfaction by monitoring the quality and quality of Konniciwa Pamulang coffee products. In this service, we use design thinking to determine quality control strategies and product quality that meet customer needs, we also use data analysis methods to find out how customers feel about quality control and product quality. The results of this service show that quality control and product quality can increase customer satisfaction. It is worth paying attention that customers like quality and high-quality products. Based on these results, Konnichiwa Pamulang Coffee continues to improve the quality and quality of its products to increase customer satisfaction.